SEBUAH IMPLEMENTASI GAME THEORY PADA STRATEGI PERSAINGAN LION AIR GROUP DAN GARUDA INDONESIA GROUP - Annisa Indah Pratiwi; Bagas Dirgantara; Trio Yonathan Teja Kusuma (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2024)
Aviation is still the people's choice of transportation today. Airlines in Indonesia are quite diverse so people consider the choice of airline. Starting from the quality of service, price, ease of reservation, etc. This case aims to analyze the strategies of AL Group and IG Group and find out which strategy is the most optimal for two parent companies. The method used is using Game Theory (Pure Strategy) which uses manual calculations and with the help of POM-QM software. In the manual calculation, the optimal value for the two parent airlines was 12. In the POM-QM software calculation, the optimal value for the two parent airlines was 11.56. Both parent airlines get the optimal point if using strategy 3 for IG Group and strategy 5 for AL Group.